Selecting accommodations for mathematics assessments: Legal and practical considerations. Issue 4 (2nd October 2018) - Peltier, Corey; Harrison, Judith R.
ABSTRACT: Multidisciplinary teams are responsible for identifying reasonable accommodations that mediate the impact of a disability and level the playing field between those with and without disabilities on high-stakes mathematics assessments. However, minimal guidance is provided to teams selecting accommodations. This article provides a decision framework for selecting accommodations to be used during mathematics assessments. The framework includes legal and practical considerations guided by evidence from case law and empirical research to aid in the selection of reasonable accommodations. To conclude, we discuss remaining unanswered questions.